Bioremediation of Soil Contamination with Polycyclic Aromatic Hydrocarbons—A Review - Carmen Otilia Rusănescu; Irina Aura Istrate; Andrei Marian Rusănescu; Gabriel Alexandru Constantin (Land)
Polycyclic aromatic hydrocarbons (PAHs) are considered hazardous pollutants due to their negative impact on the environment and human health. PAHs can accumulate and be retained in the soil, so PAH pollution is a worldwide problem. This review paper highlights the sources of PAH soil pollution, factors affecting the bioavailability of PAHs in soil, and soil bioremediation methods, as well as the advantages and limitations of the application of these methods. Aspects regarding the impact of the application of surfactants are presented in order to obtain good bioavailability during PAH bioremediation. Bioremediation techniques of soil polluted by these hydrocarbons are addressed: phytoremediation, rhizoremediation, composting, vermiremediation, micoremediation, and electrokinetic bioremediation of PAH-polluted soils. A comprehensive overview of bioremediation technologies for PAH-polluted soils is needed so that the right soil remediation technology is chosen. It has been observed the bioremediation of contaminated soils through rhizoremediation proved to be an effective process, the future of organic pollutants in interaction with plants and microbes must be researched. Vermiremediation, electrokinetic bioremediation, and microcomposting are effective processes for treating soils in situ. Phytoremediation is a sustainable and ecological method of PAH depollution. It improves soil fertility by releasing different organic matter in the soil, and it can be applied on a large scale.